Political Primordialism in Indonesia's Democratic System: An Islamic Constitutional Law Analysis of Identity-Based Preferences in the Election of Political Leaders - Anjas Saputra; Muh Imam Sejati; Mustafa; Kurniati (BAYAN: Jurnal Studi Islam dan Humaniora, 2026)
This study examines the phenomenon of political primordialism in Indonesian democracy through the perspective of Islamic constitutional law as a normative framework, focusing on how identity based preferences such as religion, ethnicity, and group affiliation influence voters’ choices in leadership elections and how these practices are evaluated within Islamic leadership principles. Departing from the tension between the ideal of rational democracy and the empirical reality of rising identity politics, this research employs a qualitative approach with a descriptive analytical method integrating empirical data and normative analysis of the principles of trustworthiness, justice, and competence. The findings show that political primordialism functions not only as a strategy for electoral mobilization by political actors but is also interpreted by voters as a form of collective identity representation, however from the perspective of Islamic constitutional law such practices tend to deviate as they prioritize identity over leadership quality which consequently weakens political rationality and undermines the principles of justice and public welfare in governance.